2004
DOI: 10.1289/ehp.6506
|View full text |Cite
|
Sign up to set email alerts
|

Potential exposure to PCBs, DDT, and PBDEs from sport-caught fish consumption in relation to breast cancer risk in Wisconsin.

Abstract: In Wisconsin, consumption of Great Lakes fish is an important source of exposure to polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT), polybrominated diphenyl ethers (PBDEs), and other halogenated hydrocarbons, all of which may act as potential risk factors for breast cancer. We examined the association between sport-caught fish consumption and breast cancer incidence as part of an ongoing population-based case-control study. We identified breast cancer cases 20-69 years of age who were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Therefore, incorporating appropriate pharmacokinetic variables may also improve risk estimates. As an example, McElroy et al found an adjusted odds ratio of 1.7 (95% confidence interval, 1.16-2.50) for premenopausal breast cancer associated with fish consumption (as a surrogate for organochlorine compounds); covariates included BMI at age 18 years and BMI-gain after that age (65). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, incorporating appropriate pharmacokinetic variables may also improve risk estimates. As an example, McElroy et al found an adjusted odds ratio of 1.7 (95% confidence interval, 1.16-2.50) for premenopausal breast cancer associated with fish consumption (as a surrogate for organochlorine compounds); covariates included BMI at age 18 years and BMI-gain after that age (65). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been widely documented that workers in industries that make, formulate or pack drugs or laboratory reagents, or those that elaborate products for industrial use, have a higher risk of developing anemia, leukemia, and cancer of bladder, stomach, lung, prostate or breast. This higher risk is considered to be mainly due to the fact that many of these compounds are mutagenic or have an estrogenic effect [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent consumption of sportcaught fish was not associated with risk of breast cancer in postmenopausal women but was associated with the risk in premenopausal women (relative risk (RR) 1.70, 95% CI 1.16-2.50) [58]. Whether the result occurred by chance or not, more studies with parallel results will help to ensure whether the contamination of PBDEs in the environment and food is associated with the development of breast cancer, especially in young and premenopausal women.…”
Section: Polybrominated Diphenyl Ethers (Pbdes)mentioning
confidence: 99%
“…McElroy and colleagues [58] evaluated recent consumption of Great Lakes fish exposed to organic pollutants, including PBDEs. Recent consumption of sportcaught fish was not associated with risk of breast cancer in postmenopausal women but was associated with the risk in premenopausal women (relative risk (RR) 1.70, 95% CI 1.16-2.50) [58].…”
Section: Polybrominated Diphenyl Ethers (Pbdes)mentioning
confidence: 99%